Implementing the Balanced Scorecard in Government Organizations: A Systematic Literature Review - Wahyono Wahyono; Yuliusman Yuliusman; Wirmie Eka Putra; Fitrini Mansur (Universitas Muhammadiyah Gorontalo, 2025)
The Balanced Scorecard (BSC) has evolved into a widely adopted strategic performance management framework in government organizations, supporting accountability, transparency, and organizational effectiveness. However, its implementation across public-sector contexts remains fragmented, with variations in organizational settings, leadership commitment, stakeholder engagement, and digital transformation. This study aims to systematically review the existing literature on BSC implementation in government organizations, identify major research trends, examine implementation approaches, and highlight challenges and future research opportunities. A Systematic Literature Review (SLR) was conducted following a structured and transparent review protocol. Literature was retrieved from the Scopus and Web of Science databases using predefined search criteria covering publications from 2000 to 2024. From an initial pool of 1,709 records, 36 peer-reviewed articles met the eligibility criteria and were analyzed. The findings indicate that BSC has become an important instrument for aligning strategic objectives with operational activities across various levels of government. Recent studies increasingly emphasize integrating the BSC with digital governance, e-government initiatives, and data-driven decision-making to enhance public-sector performance. Nevertheless, implementation effectiveness remains constrained by organizational culture, leadership commitment, stakeholder involvement, bureaucratic complexity, and the need for context-specific performance indicators. The review also reveals limited comparative and longitudinal evidence across government settings, suggesting opportunities for further investigation. Overall, this study synthesizes the current state of knowledge and provides practical and theoretical insights for researchers and policymakers seeking to strengthen strategic performance management through Balanced Scorecard implementation in the public sector.